Sosialisasi Pentingnya Penggunaan KB dalam Kesehatan Reproduksi di Desa Mosso - gusnawati, Yesi; Irmayanti AR (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction Uncontrolled population growth is one of the major challenges in development in Indonesia. The Family Planning (FP) program is a government initiative aimed at controlling birth rates and improving the quality of family life. However, public understanding of family planning remains limited, particularly in rural areas. Therefore, FP counseling is essential to raise awareness and increase public participation, especially among couples of reproductive age, in planning a healthy and responsible family. Objective To increase public knowledge about the benefits of the Family Planning program and to improve participation among couples of reproductive age in using contraceptive methods. Additionally, to reduce the number of unplanned pregnancies. Method The counseling activity was conducted using an interactive lecture method, accompanied by a Q&A session, leaflet distribution, and demonstrations of contraceptive use. The activity took place over one day at the Mosso Village Hall and targeted couples of reproductive age (CRA). Family planning services such as contraceptive injections and pill distribution were also provided. Result The counseling activity was attended by 30 couples of reproductive age. After the session, 80% of participants showed improved understanding of the benefits of family planning and contraceptive methods. Most participants stated that the session helped them better understand the importance of family planning. Conclusion Based on the results of the Family Planning counseling activity in Mosso Village, it can be concluded that the program successfully increased public knowledge and awareness of the importance of family planning. Participants' enthusiasm indicated that an interactive counseling approach and direct service provision were highly effective. It is expected that similar activities will continue to be held regularly to expand their reach and impact within the community.